Neurobiology of the lateral septum: regulation of social behavior. Issue 1 (January 2022) - Menon, Rohit; Süß, Theresa; Oliveira, Vinícius Elias de Moura; Neumann, Inga D.; Bludau, Anna
Abstract : Social interactions are essential for mammalian life and are regulated by evolutionary conserved neuronal mechanisms. An individual's internal state, experiences, and the nature of the social stimulus are critical for determining apt responses to social situations. The lateral septum (LS) – a structure of the basal forebrain – integrates abundant cortical and subcortical inputs, and projects to multiple downstream regions to generate appropriate behavioral responses. Although incoming cognitive information is indispensable for contextualizing a social stimulus, neuromodulatory information related to the internal state of the organism significantly influences the behavioral outcome as well. This review article provides an overview of the neuroanatomical properties of the LS, and examines its neurochemical (neuropeptidergic and hormonal) signaling, which provide the neuromodulatory information essential for fine-tuning social behavior across the lifespan. Highlights: The lateral septum (LS) is neurochemically diverse and ideally positioned to serve as a relay center, which integrates incoming cortical information about the social environment with the internal state and prior social experiences, and then transmits this information to downstream executive regions. Existing evidence from rodents implicates different neuronal subpopulations expressing receptors for various neuropeptides and hormones within the LS in modulating a variety of social behaviors, including aggression, sexual and parental behavior, as well as general interactions with a conspecific. This review article suggests that the abovementioned neuromodulatory signals often arising from limbic brain regions communicate the internal state of the organism and influence the integration of cognitive input into neuronal codes in the LS to modulate social behavior under basal and stressful conditions.